2018
DOI: 10.1371/journal.pgen.1007169
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in THAP1/DYT6 reveal that diverse dystonia genes disrupt similar neuronal pathways and functions

Abstract: Dystonia is characterized by involuntary muscle contractions. Its many forms are genetically, phenotypically and etiologically diverse and it is unknown whether their pathogenesis converges on shared pathways. Mutations in THAP1 [THAP (Thanatos-associated protein) domain containing, apoptosis associated protein 1], a ubiquitously expressed transcription factor with DNA binding and protein-interaction domains, cause dystonia, DYT6. There is a unique, neuronal 50-kDa Thap1-like immunoreactive species, and Thap1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 85 publications
5
75
0
1
Order By: Relevance
“…More recently, increased lysosomal degradation has been identified as the molecular basis for decreased D2 receptor density in DYT1 dystonia, once again reinforcing the increasing central convergent role for D2R dysfunction in dystonia (Bonsi et al, 2019). The extent to which these results can be extended to focal forms, such as cervical dystonia, remains unclear; however, it is interesting to note that recently identified genes associated with a cranio-cervical phenotype, including GNAL, THAP1, and ANO3, share common roles in striatal signal transduction (Charlesworth et al, 2012;Kumar et al, 2014;Zakirova et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…More recently, increased lysosomal degradation has been identified as the molecular basis for decreased D2 receptor density in DYT1 dystonia, once again reinforcing the increasing central convergent role for D2R dysfunction in dystonia (Bonsi et al, 2019). The extent to which these results can be extended to focal forms, such as cervical dystonia, remains unclear; however, it is interesting to note that recently identified genes associated with a cranio-cervical phenotype, including GNAL, THAP1, and ANO3, share common roles in striatal signal transduction (Charlesworth et al, 2012;Kumar et al, 2014;Zakirova et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Abnormalities in striatal plasticity are thought to be a pathogenic mechanism common to all forms of dystonia (Peterson et al, 2010). In animal models of rare, childhood onset generalized dystonia (DYT1, DYT6), highly specific cortico-striatal plasticity abnormalities have been observed in vitro (Maltese et al, 2017;Martella et al, 2009;Pisani et al, 2006;Zakirova et al, 2018). Whether defective corticostriatal plasticity contributes to the expression of the common late onset focal forms, including cervical dystonia, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our research identified the dysregulation of PKR‐eIF2α signaling pathway as a consequence of P222L mutation in DYT16 . Subsequently DYT1, DYT6, as well as the sporadic cervical dystonia also were reported to show an impairment of the eIF2α signaling pathway . Although we could not analyze eIF2α dysregulation with expression of FS mutant protein in the transient expression system, it is worth a mention that a spontaneously arisen, recessive insertion mutation in Prkra identified at the Jackson Laboratory (JAX) results in a progressive dystonia, kinked tails, and mortality in mice.…”
Section: Discussionmentioning
confidence: 89%
“…25 Subsequently DYT1, DYT6, as well as the sporadic cervical dystonia also were reported to show an impairment of the eIF2α signaling pathway. [48][49][50][51] Although we could not analyze eIF2α dysregulation with expression of FS mutant protein in the transient expression system, it is worth a mention that a spontaneously arisen, recessive insertion mutation in Prkra identified at the Jackson Laboratory (JAX) results in a progressive dystonia, 52 kinked tails, and mortality in mice. Some neurons in the dorsal root ganglia and the trigeminal ganglion were apoptotic in the homozygous mutant mice, consistent with the observed neurodegenerative phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…Given the central role of MSNs in receiving and gating synaptic inputs from cortical and thalamic glutamatergic neurons, this suggests that disruption of postsynaptic function in MSNs through mutations in multiple DYT genes may be important in dystonia pathogenesis. In support of this hypothesis are the following observations: (i) abnormal plasticity and loss of synaptic downscaling at cortico-striatal synapses has been shown to be a dystonia endophenotype shared by different genetic animal models of dystonia (Martella et al, 2014;Calabresi et al, 2016;Maltese et al, 2017;Zakirova et al, 2018;Yu-Taeger et al, 2019); (ii) ADCY5 and GNAL, two DYT genes, form part of the signalling transduction machinery in response to stimulation of dopaminergic and adenosinergic signaling in MSNs (Herve, 2011;Goodchild et al, 2013); (iii) and finally, Insomniac and nca (Drosophila homologues of KCTD17 and HPCA, respectively, both of which are DYT genes in the putamen "cyan" module) have been found to modulate sleep in Drosophila through disruption of dopaminergic post-synaptic signalling (Pfeiffenberger and Allada, 2012;Chen et al, 2019;Kikuma et al, 2019).…”
Section: Other Neuronal Cell Types Highlighted By Our Ewce-and Wgcna-mentioning
confidence: 88%